(untitled) (Tejganga Darpan, 2026)
The Government of Nepal has the provision of free mid- day meal (tiffin) to the primary level students in community school. It is one of the key educational and nutritional interventions intended to support early childhood development and the foundational learning of children. The main objective of this program is to improve student health, increase school participation, enhance regularity and strengthening academic achievement. This study explores the effectiveness of the tiffin program in the Community School of Panauti municipality of Kavrepalanchowk district. A total of 36 student and 15 parents were participated in this study. Questionnaire, class observation, attendance and parental interviews were taken for the collection of data on focusing children’s regularity, overall health condition, children’s motivation to the learning platform. It is found that the positive impact of the program on regularity, classroom participation, student interest on going to the school, nutritional awareness and parental involvement. This study concludes that the mid day meal (tiffin) program is an effective tool for promoting equitable access to education, enhancing the learning environment and reducing absenteeism. Despite the positive outcomes, the programs face some challenges such as inconsistent budgeting, occasional shortages of locally grown food items and need for the stronger community level monitoring. This research suggests ongoing expansion, better coordination among stakeholders, regular evaluation, integration of nutritional education within the school curriculum and diversification of meal varieties. The article may contribute valuable localized evidence to support the sustainability of Nepal’s school mid-day meal initiatives.